Addressing the double burden of malnutrition in Egypt: Report on a stakeholder workshop on key challenges, policy solutions, and research opportunities - Shokry, Nada; Jovanovic, Nina; Kurdi, Sikandra; Hamdy, Adham; Elkaramany, Mohamed (International Food Policy Research Institute, 2025)
Key messages Parliamentarians, researchers, and development practitioners shared perspectives on the double burden of malnutrition in Egypt in roundtable discussions. Infrastructure gaps and policy and research strategy fragmentation are highlighted as challenges to accessibility of healthy food. Aggressive ads/media environment and inefficient nutrition education programs are regarded as negatively impacting consumer behavior. Economic factors are widely identified as a major driver of malnutrition. Recommended solutions include raising nutrition literacy, transitioning from food subsidies to vouchers, improving nutrition services infrastructure, taxing unhealthy foods, and fortifying staple foods. Participants called for continued dialogue between researchers and policymakers.